2011
DOI: 10.1080/17457300.2011.551942
|View full text |Cite
|
Sign up to set email alerts
|

Average out-of-pocket healthcare and work-loss costs of traffic injuries in Karachi, Pakistan

Abstract: The objective of this study was to assess the average out-of-pocket healthcare and work-loss costs of road traffic injuries (RTI) in Karachi. In this cross-sectional study, RTI patients presenting to the five trauma centres in Karachi were contacted using stratified sampling to report their inpatient and outpatient expenses, the time spent in hospital and their average monthly income. These costs were compared among different categories of patient-related variables using analysis of variance test. Out of 341 R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 17 publications
0
16
1
Order By: Relevance
“…8 A recent study on cost of road traffic injury showed an average out of pocket expense on health care of USD 271 (SD:441) and an average loss of work of about USD 67 (SD:132), with a greater loss among victims who were the breadwinners. 20 The average health care cost was greater than average monthly household income in more than 80% of cases. 20 …”
Section: Economic and Social Impactmentioning
confidence: 98%
See 1 more Smart Citation
“…8 A recent study on cost of road traffic injury showed an average out of pocket expense on health care of USD 271 (SD:441) and an average loss of work of about USD 67 (SD:132), with a greater loss among victims who were the breadwinners. 20 The average health care cost was greater than average monthly household income in more than 80% of cases. 20 …”
Section: Economic and Social Impactmentioning
confidence: 98%
“…20 The average health care cost was greater than average monthly household income in more than 80% of cases. 20 …”
Section: Economic and Social Impactmentioning
confidence: 98%
“…Also, the study captured cost of care during hospitalisation and up to 12 months postdischarge. Similarly, studies done in other South East Asia Region countries such as in India, Bangladesh,21 Pakistan15 and Vietnam22 have reported OOP expenditure in the range US$300–400. However, these studies focused on persons who had been in road traffic injuries which usually lead to severe injuries.…”
Section: Discussionmentioning
confidence: 70%
“…The Korangi Town has many important place for commercial activities, having many industries which one important industrial place known as K. I. T. E. (Korangi Industrial Trading Estate). This town consists of complex road networks resulting maximum number of RTAs, while vulnerable road user group especially in industrial area becomes a major cause of death [25][26][27][28][29][30][31][32]. The victims' record (information) is confirmed from RTI surveillance program (Karachi).…”
Section: Variation Respectively Years: 2008 2009-12mentioning
confidence: 99%